WIPF2 promotes Shigella flexneri actin‐based motility and cell‐to‐cell spread. (26th August 2019) - Michard, Céline; Yum, Lauren K.; Agaisse, Hervé
Abstract: Shigella flexneri is an intracellular pathogen that disseminates in colonic epithelial cells through actin‐based motility and formation of membrane protrusions at cell–cell contacts, that project into adjacent cells and resolve into vacuoles, from which the pathogen escapes, thereby achieving cell‐to‐cell spread. Actin nucleation at the bacterial pole relies on the recruitment of the nucleation‐promoting factor N‐WASP, which activates the actin nucleator ARP2/3. In cells, the vast majority of N‐WASP exists as a complex with WIP. The involvement of WIP in N‐WASP‐dependent actin‐based motility of various pathogens, including vaccinia virus and S. flexneri, has been highly controversial. Here, we show that WIPF2 was the only WIP family member expressed in the human colonic epithelial cell line HT‐29, and its depletion impaired S. flexneri dissemination. WIPF2 depletion increased the number of cytosolic bacteria lacking actin tails (non‐motile) and decreased the velocity of motile bacteria. This correlated with a decrease in the recruitment of N‐WASP to the bacterial pole, and among N‐WASP‐positive bacteria, a decrease in actin tail‐positive bacteria, suggesting that WIPF2 is required for N‐WASP recruitment and activation at the bacterial pole. In addition, when motile bacteria formed protrusions, WIPF2 depletion decreased the number of membrane protrusions that successfully resolved into vacuoles. Abstract : The intracellular pathogen Shigella flexneri disseminates in colonic epithelial cells through actin‐based motility and membrane protrusions at cell‐cell contacts. Actin nucleation requires the nucleation‐promoting factor N‐WASP, most of which exists as a complex with WIP. The involvement of WIP in N‐WASP‐dependent actin‐based motility of various pathogens has been controversial, but this study further elucidates and shows the importance of WIP in pathogen spread.